Implementation of the Madrasah Curriculum 1984 to 2013 in Al-Washliyah Private Madrasah 30 City of Binjai - Hannum, Ikhsanti; Dahlan, Zaini; Budianti, Yusnaili (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This paper will discuss how the private Madrasah Aliyah Al Washliyah 30 Binjai City applies the madrasa curriculum. Since the first madrasah (in 1990) until now, the madrasa curriculum has changed 5 times. In fact, the Department or the Ministry of Religion has determined the subjects of Fiqh, Qur'an Hadith, Akidah Akhlak and Islamic Cultural History as curriculum content. Descriptive research method with a qualitative approach, used in writing. The main data were obtained through interview techniques and observations of several madrasa documents. The result of the research is Madrasah Aliyah Al Washliyah 30 Binjai City applies all religious subjects at the madrasa.